Accuracy and reliability of the Wattbike ergometer : An Australian perspective - Ebert, T. R.; Dingley, A.; Staneff, T.; Plowmann, J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
The Wattbike is a stationary wind-braked cycle ergometer developed in the United Kingdom over the past 5 years. With input and feedback from Great Britain cycling "mastermind" Peter Keen and sport scientist Scott Gardner, the ergometer utilises the same wind resistance concepts adopted by Concept II rowing ergometers. At ~$3500 Australia Dollars the ergometer is surprisingly inexpensive. In addition the Wattbike provides users with a wide range of resistance settings that claim to simulate hill climbing and drafting/motorpacing. An additional feature of interest is the quantification of right leg and left leg torque. Thus far we are unaware of independent evaluations of the Wattbike ergometer accuracy and reliability. Methods Five Wattbikes were purchased by the ASC NTID program and assembled in Adelaide. In addition, a Wattbike was loaned to the AIS for evaluation purposes. The details of the Wattbike can are presented on the company`s website (www.wattbike.com). The ergometer uses a strain gauge technology to measure chain tension during the pedal stroke. Based on chain speed and chain tension, the torque during the pedal stroke is estimated allowing power and work to be calculated. The entire bike weighs around 55kg and the construction of the ergometer appears to be for the fitness market vs the high-end racing market. As a result, the nonconventional bicycle components are used and width between pedals tends to be wider than observed on race bikes (180 vs 150mm). A dynamic calibration rig was used to evaluate accuracy and reliability of the ergometer. At SASI five Wattbikes were evaluated twice to establish power output errors over 100 - 1500 Watts. Testing was performed using an incremental intensity protocol. An additional, Wattbike at the AIS in Canberra was also tested for accuracy using a similar testing protocol. The accuracy of the Wattbike was also examined over prolonged tests durations 30-60min to examine whether the measurement error drifted. Results Additional dynamic calibration trials performed at the AIS on one Wattbike established that power output measurement over 30 and 60min steady state trials were stable and resistant to any form of "drift". Summary Preliminary evaluations of the Wattbike with a dynamic calibration rig demonstrate that accuracy and reliability can differ between Wattbikes, but overall, the accuracy of these ergometers tends to be within 2.5% up to ~1500W and measurements tend to be resistant to drift over prolonged trials lasting 30-60min. Further research examining maximal mean power output produced on the Wattbike compared to field efforts other ergometers is warranted.